Synergistic Antitumor Effect of Doxorubicin and Tacrolimus (FK506) on Hepatocellular Carcinoma Cell Lines. (20th February 2014) - Capone, Francesca; Guerriero, Eliana; Sorice, Angela; Colonna, Giovanni; Storti, Gabriella; Pagliuca, Jessica; Castello, Giuseppe; Costantini, Susan
Abstract : Hepatocellular carcinoma is the fifth most common cancer worldwide and shows a complex clinical course, poor response to pharmacological treatment, and a severe prognosis. Thus, the aim of this study was to investigate whether tacrolimus (FK506) has synergistic antitumor effects with doxorubicin on two human hepatocellular carcinoma cell lines, Huh7 and HepG2. Cell viability was analyzed by Sulforhodamine B assay and synergic effect was evaluated by the software CalcuSyn. Cell apoptosis was evaluated using Annexin V and Dead Cell assay. Apoptosis-related protein PARP-1 cleaved and autophagy-related protein expressions (Beclin-1 and LC3B) were measured by western blotting analysis. Cytokines concentration in cellular supernatants after treatments was studied by Bio-Plex assay. Interestingly the formulation with doxorubicin and tacrolimus induced higher cytotoxicity level on tumor cells than single treatment. Moreover, our results showed that the mechanisms involved were (i) a strong cell apoptosis induction, (ii) contemporaneous decrease of autophagy activation, understood as prosurvival process, and (iii) downregulation of proinflammatory cytokines. In conclusion, future studies could relate to the doxorubicin/tacrolimus combination effects in mice models bearing HCC in order to see if this formulation could be useful in HCC treatment.